(untitled) (Veterinary Science, 2025)
The c-MYC oncogene is emerging as a key regulator in the pathogenesis of canine tumors and is established as a priority therapeutic target. This gene is vital for cellular homeostasis, being involved in processes such as proliferation, differentiation, metabolism, and apoptosis. Its deregulation, frequently due to gene amplification or chromosomal rearrangements, has been associated with various canine neoplasias: transmissible venereal tumor TVT, mammary tumors, osteosarcomas, and prostate and ocular carcinomas. In the case of TVT, the insertion of LINE-1 elements in c-MYC highlights it as a relevant diagnostic marker. Abnormal c-MYC expression is associated with aggressiveness and rapid tumor progression, consolidating its potential as a diagnostic marker and therapeutic target. Although direct c-MYC inhibition presents technical challenges, current strategies seek to modulate its activity by inhibiting upstream signaling pathways or modifying its protein interactions. These advances could significantly improve the treatment of canine neoplasia. In comparative oncology, canine models are valuable for studying human tumor biology due to pathological similarities and spontaneous tumors. Analysis of c-MYC offers a platform for investigating shared oncogenic mechanisms and evaluating therapeutic interventions before their application in human medicine. Thus, the study of c-MYC is crucial in cancer research in both veterinary and human medicine